The Utility of Fluorescence in Situ Hybridization for Diagnosis and Surveillance of Bladder Urothelial Carcinoma - Huang, Jian-Wen; Mu, Jia-Gui; Li, Yun-Wei; Gan, Xiu-Guo; Song, Lu-Jie; Gu, Bao-Jun; Fu, Qiang; Xu, Yue-Min; An, Rui-Hua (Urology Journal, 2014)
Purpose: To evaluate the clinical value of fluorescence in situ hybridization (FISH) for diagnosis and surveillance of bladder urothelial carcinoma (BUC). Materials and Methods: Between November 2010 and December 2013, patients suspected of having BUC were examined using urine cytology and FISH assay. Based on histopathological examination results, FISH results were compared with urine cytology. In addition, patients with a history of non-muscle invasive BUC were also examined using urine cytology and FISH assay at the first time of visit and then monitored with cystoscopy during follow-up period. Results: A total of 162 patients included in this study and 12 patients were excluded due to uninformative FISH assays. The remaining 150 patients consisted of 108 patients suspected for BUC and 42 patients with a history of non-muscle invasive BUC. The sensitivities of FISH analysis and urine cytology were 72.8% and 27.2%, respectively, and the difference was statistically significant (P <.05). Difference between specificity of urine cytology (100%) and FISH assay (85%) was not statistically significant (P >.05). At the first visit, of 42 patients, one patient had positive cystoscopy, and FISH assay was positive in 26 of 41 patients with negative cystoscopy. During the follow-up period (mean, 29.5 months), 18 of 26 patients developed recurrence, and recurrence occurred in only one of 15 patients with negative FISH analysis. Conclusion: Our results suggest that FISH analysis can be used as a non-invasive diagnostic tool for patients suspected of having new BUC. In addition, FISH analysis may provide important prognostic information to better define the individual risk for BUC recurrence.